(untitled) (14th CONSTRUCTAL LAW CONFERENCE | 10-11 October 2024, Bucharest, Romania, 2024)
Ceramic foams are promising as absorber materials for volumetric solar receivers (VSR) in concentrated solar thermal power (CSP) systems. The temperature distribution of the VSR is very important to ensure that it operates efficiently and steadily. This study aims to simulate and analyze the temperature distribution within a VSR considering both the solid and fluid phases. The modelling of the open-cell volumetric receiver employs combined volume-averaged equations, assuming the ceramic foam to possess isotropic and homogeneous properties. To assess the pressure-drop in the VSR a non-Darcian model is adopted. A local thermal non-equilibrium (LTNE) model is implemented to describe the energy equations for both the solid and fluid phases. Additionally, the study considers the influence of solar radiation as a heat source on the solid phase. The heat transfer between the surfaces of the volumetric solar air receiver’s struts is calculated using the P1 model. At the same time, a macroscopic approach is utilized to evaluate the thermal profile of the ceramic foam. This study also aims to assess the impact of the VSR’s porosity and cell size variation on the outlet air temperature. Moreover, the flow scheme of the flowing air, concerning the incident of concentrated radiation, is considered.